Plan de negocios para la creación de un restaurante campestre (2019)
The present business idea arises as a response to the high demand of the gastronomic product of Barbosa, Santander, because, in this municipality, there are not many restaurant options for tourists who come to the area searching places with comfortable, pleasant and that offers a quality service and products to eat with the family. For these reasons the present business plan is created, called El Molino, in order to respond to all the needs of tourists visiting this area, offering them the best infrastructure in the region, enabled with recreational parks, large parking spaces and those who can take a lunch in the middle of the road to their final destination. In addition to this, El Molino restaurant will have qualified human capital for customer service and preparation of dishes, which have experience in the food and beverage sector. El Molino will also have as an attraction the type of food it will offer, since it will be typical of the region and grilled meats. The prices that will be managed are affordable for families of strata 3, 4, 5 and 6 that look for comfort and good food.